(untitled) (American Journal of Islam and Society, 2014)
Abdelwahab Meddeb’s Islam and the Challenge of Civilization offers new perspectives on and fresh associations among historical events in a way that draws the curtain and adjusts the view among Muslim public intellectuals. Situated within the broad scholarship of Islamic thought, it engages critically and creatively with various doctrinal issues that are being manipulated by some Muslim opinion leaders to support their own bellicose positions. The author reveals the linkages between Islam and other revealed faiths, especially during the former’s “golden age,” which witnessed productive encounters between theologians and philosophers of diverse religious orientations. The book comprises six chapters in addition to a prologue, an epilogue, notes, and two appendices. In his prologue, the author argues that “violence produced by belief is not unique to Islam but finds virulent expression even among beliefs issuing from the Indian subcontinent” (p. viii) and emphasizes the need for a “check on violence via the return to context” (p. ix). He seeks to awaken Muslims “to the fact that times have changed” (p. x) and that “the world is a different place” (p. x), which is why “when it comes to religious identity” (p. x), Islam cannot continue to “perceive Christianity as if it were still its medieval antagonist, despite modern notions of nations and peoples that have circumscribed the religion” (p. x). The following statement sums up the author’s thesis: “In short, if Islam is to be cured of its current affliction, it must get to that post-Islamic, post-religious place where Christianity and Judaism have managed to arrive” (p. x). This sounds interesting and prompts a meticulous reader to watch out for an elaboration thereof. Unfortunately, such an elaboration never appears ...